Cover Crop Management on the Southern High Plains: Impacts on Crop Productivity and Soil Water Depletion - Lisa L. Baxter; Charles P. West; C. Philip Brown; Paul E. Green (Animals, 2021)
The imminent depletion of the Ogallala Aquifer demands innovative cropping alternatives. Even though the benefits of cover crops are well recognized, adoption has been slow in the Southern High Plains (SHP) of the United States because of concerns that cover crops withdraw soil water to the detriment of the summer crops. This small plot experiment tested the interacting effects—production, soil water depletion of the cover crops, and subsequent teff [Eragrostis tef (Zucc.) Trotter] summer hay crops—of irrigation and tillage management with five cover crop types to identify low-risk cover crop practices in the drought-prone SHP. Dryland rye (Secale cereale L.) produced modest forage biomass (>1000 kg ha−1), even in a dry year, but it was found that light irrigation should be used to ensure adequate forage supply (>1200 kg ha−1) if winter grazing is desired. No-till management and timely termination of the winter cover crops were crucial to reducing the negative impact of winter crops on summer teff production. The results indicated no detriment to soil water content that was attributable to planting no-till cover crops compared with the conventional practice of winter fallow. Therefore, producers could take advantage of the soil-conserving attributes of high-quality winter forage cover crops without experiencing significant soil water depletion.